Solving by substitution method.
If we clear y in equation 1, we get:
![y=3+x](https://img.qammunity.org/2023/formulas/mathematics/college/ur6e4ns4vjppypxpxeknmniex0to43bmcx.png)
Now, if we substitute this result into equation 2, we have
![3x+(3+x)=-1](https://img.qammunity.org/2023/formulas/mathematics/college/yyouk8d2ow3az0bu9lvwe1wpazr430qfor.png)
By clearing parenthesis, we get 3x+3+x=-1.
Now, by combining similar terms, we obtain
![4x+3=-1](https://img.qammunity.org/2023/formulas/mathematics/college/7rbyqg6bpk38ru97m3jj220pllvh4e0xf6.png)
If we move +3 to the right hand side as -3, we have
![\begin{gathered} 4x=-1-3 \\ 4x=-4 \\ x=-(4)/(4) \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3f8r42otoviljxo0qyixf39xs9bf4trwxw.png)
Finally, by substituting this result into out first equation, we get
![\begin{gathered} y=3+(-1) \\ y=3-1 \\ y=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dudz1wt9plalkst0v107l4bz0jo808zq8h.png)
Therefore, the solution of the system is x=-1 and y=2.